Pengelolaan Kelembagaan Lelang Lebak Lebung dan Perilaku Nelayan di Kabupaten Muara Enim Provinsi Sumatera Selatan - Enik Afri Yanti; Arif Satria; Basita Ginting Sugihen (Jurnal Penyuluhan, 2015)
The study aims to (1) Analyzing attitude of the fishermen towards management system in Lebak Lebung (knowladge, behaviour, and manner), (2) to describing auction system of Lebak Lebung, (3) and to analyze the external and internal characteristic between the institutional and the fishermen towards open waters managed in Lebak Lebung. The study was conducted using survay methods thourgh decriptive analysis and corellation methode which the samples of this study are 100 fishermen in Muara Enim –Sub distict-. The result showed that (1) Lebak Lebung is the open water district which consist of river area and land that forms marshes (lebak) and low land that watery (lebung). Lebak Lebung will be a fishes breeding in ebb season, and in the flow season Lebak Lebung used by villager to catch fishes. The ownership of fish resources in Lebak Lebung will be given to Pegemin auction as a winner of area Lebak Lebung thourgh aution system. The aims of Lebak Lebung-auction is to obtain the income areas, and conservation of Lebuk Lebung, and avoid the confilcts between fishermen.(2) the highly behaviour : knowladge, behaviour, and manner of fihermen in Lubuk Lebung auctions management. (3) Internal characteristic, Lebak lebung institutional and external characteristics that relating to the behavior of fishermen is the level of education, the number of dependents experience of fishermen effort, income of the fishermen, rule, punishment, the performance of fishermen group, the government policy.Keywords: auction, fishermen custom, institutional, Lebak Lebung